(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
Alternatives to the dominant public sphere and associated dialogue are especially important for underrepresented groups. These alternatives allow for groups to create their own dialogues that can then be used to change the direction of the larger discussion. While the Internet seems to be the perfect tool for these alternative dialogues to be created, the feasibility of using the Internet to take the next step into mainstream dialogue remains unclear. The black blogosphere is one alternative information stream pushing back. This chapter examines the way in which the black blogosphere discusses news stories and offers alternatives to the mainstream discourse, and why it is crucial that these alternative public spheres are available.